2001
DOI: 10.1046/j.1461-0248.2001.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasites reduce territorial behaviour in red grouse (Lagopus lagopus scoticus)

Abstract: Hypotheses for the cause of population cycles have focused on the role of intrinsic mechanisms such as spacing behaviour and extrinsic mechanisms such as parasitism and predation. This paper examines the interaction between the two dominant hypotheses in the cycles of red grouse, parasitism and spacing behaviour. The influence of the caecal nematode, Trichostrongylus tenuis, on male aggressiveness was investigated using two approaches. First, the territorial behaviour of a group of male grouse experimentally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 24 publications
5
46
0
Order By: Relevance
“…We found relatively similar treatment effects on flight call rate: dosed old males tended to perform more flight calls than challenged old males, while the reverse tendency was observed in young males. This result for old males was consistent with a previous experiment showing that parasite removal enhances flight call rate in spring (Fox and Hudson 2001). Ground calls are typical aggressive calls, so the observation that parasites limit ground call rate, and particularly in old males, was consistent with the initial hypothesis.…”
Section: Effects Of Treatment On Parasite Intensities and Autumn Terrsupporting
confidence: 91%
See 1 more Smart Citation
“…We found relatively similar treatment effects on flight call rate: dosed old males tended to perform more flight calls than challenged old males, while the reverse tendency was observed in young males. This result for old males was consistent with a previous experiment showing that parasite removal enhances flight call rate in spring (Fox and Hudson 2001). Ground calls are typical aggressive calls, so the observation that parasites limit ground call rate, and particularly in old males, was consistent with the initial hypothesis.…”
Section: Effects Of Treatment On Parasite Intensities and Autumn Terrsupporting
confidence: 91%
“…In this study, we focus on the effect of parasite intensity on testosterone-dependent territorial behaviour. Previous work has shown that parasites reduce aspects of red grouse sexual and aggressive behaviour in spring: males cleared of their nematode parasites performed more flight calls and won more territorial contests than control males (Fox and Hudson 2001). However, worm intensities are usually higher in autumn than in spring (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fox and Hudson (2001) found that cecal nematodes (Trichostrongylus tenuis) could impact territoriality in red grouse. The louping ill virus, which is transmitted by the tick Ixodes ricinus from sheep to red grouse can result in lower densities, higher mortality, and reduced harvest .…”
Section: Predation Parasites and Pathogens 10 -12mentioning
confidence: 99%
“…A meta-analysis of these studies showed that the evidence for androgen-induced immunosuppression is ambiguous for birds (Roberts et al 2004). Fewer studies have taken into account that infections might have a suppressive effect on the expression of social and reproductive behavior via an effect of the immune system on the hypothalamus pituitary axis (see Hart 1990;Hillgarth and Wingfield 1997;Fox and Hudson 2001). That such an alternative pathway exists is suggested by a study in which male house finches, Carpodacus mexicanus, infected with coccidian parasites were found to have lower levels of testosterone than uninfected males (Duckworth et al 2001).…”
Section: Introductionmentioning
confidence: 99%